Electronic worksheet on global warming with ethno-socioscientific issues integration to promote deep learning - Rizal, Haryanti Putri; Rahmadhani, Aulia; Aira, Cinta Dian; Tambing, Afriani Aris (Indonesian Journal of Science and Mathematics Education, 2025)
The growing challenge of global warming underscores the need for innovative learning resources that connect scientific concepts to real-world issues, as existing materials often lack contextualization. This study aimed to develop and evaluate an electronic worksheet (e-worksheet) on global warming, integrating Ethno-Socioscientific Issues (E-SSI) with the Problem-Based Learning (PBL) model for junior high school students. The research utilized the Design and Development Research (DDR) approach. The e-worksheet integrated global warming as a socioscientific issue (SSI), drawing on Mandar's local wisdom for mitigation within the PBL framework. Validation by six experts using Aiken's V, along with limited trials involving 18 teachers and 10 students, assessed its validity and practicality. Results showed a high validity index (V = 0.89) and very practical ratings from teachers (92.96%) and students (83.59%). These findings imply that the developed e-worksheet is valid and practical in promoting meaningful, mindful, and joyful learning, and it offers an innovative resource that bridges global scientific concepts with local cultural practices, supporting deep learning in science education. This approach has implications for STEM education by integrating scientific understanding, problem-solving, and technological skills within the context of relevant SSI and culture.